The effect of Nigella sativa (black cumin seeds) and Zingiber officinale (Ginger rhizome) Essential Oils on Multidrug-Resistant Bacteria - Aziz, Shawnm Ahmed; Salih, Tara Faeq M.; Hamachawash, Kwestan Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2019)
Antibiotic resistance is growing and has limited the ability of physician's treatment decisions. Discovery of new, effective and safe substances that prevent troublesome infections is greatly needed to provide alternative therapeutic options. This study evaluated the antibacterial and synergistic effect of Hydro extracts of two plants essential oils of black seed (Nigella sativa) and ginger (Zingiber officinale) rhizome each alone and in combination, against selected different strains of gram negative and gram positive multidrug-resistant bacteria (Klebsiella pneumonia, Acinetobacter baumannii, Pseudomonas aeruginosa , Escherichia coli and Methicillin Resistant Staphylococcus aureus ) isolated from burn patients. The isolated were identified basing upon their colony characteristics, gram-staining, motility and biochemical tests according to standard microbiological techniques. All the isolates were tested for their susceptibility to different antibiotics and compared to the interpretive chart zone sizes. The antibacterial effect of essential oils was conducted against all isolates by disk diffusion assay, the minimum inhibitory concentrations and the minimum bactericidal concentrations of the plant essential oils were processed by using micro-dilution technique. The results indicated that all the different strains of Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Escherichia coli that were tested against 100% concentration of essential oils; there was no recorded zone of inhibition. However, for the different strains of Methicillin Resistant Staphylococcus aureus, different zones of inhibition where obtained for Nigella sativa oil singly and combination of Nigella sativa with Zingiber officinale at different dilutions 100%, 75%, 50%, 25%, 12.5%, 6.25% and 3.12%. Nigella sativa oil alone presents inhibition zones at concentration 100% ranged between (10mm) to (34mm), while Zingiber officinale oil extracts alone had no significant antibacterial effect. In addition, combination of both oil extracts at 100% concentration showed inhibition zone greatest than the standards antibiotics which ranged between (12mm) to (52mm). Synergistic effect was noticed in combination of Nigella sativa, Zingiber officinale oil extracts and Antibiotics. The combination of both oil extracts of Nigella sativa oil and Zingiber officinale oil showed an excellent antibacterial and synergistic activity against Methicillin Resistant Staphylococcus aureus.
Keywords: Plants essential oil; Multidrug resistances; Nigella sativa; Zingiber officinale; Antimicrobial activity; Synergistic effects